2019
DOI: 10.1186/s12891-019-2764-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiological features of high tibial osteotomy and tibial condylar valgus osteotomy

Abstract: Background The purpose of this study was to compare radiological features between high tibial osteotomy (HTO) and tibial condylar valgus osteotomy (TCVO), in order to define the radiological indication criteria for TCVO. Methods Thirty-two cases involving 35 knees that had undergone HTO and the same number that had undergone TCVO for knee osteoarthritis were retrospectively evaluated. Characteristics of both groups did not differ significantly. Lower limb alignment, bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 54 publications
1
23
0
1
Order By: Relevance
“…The shape of tibia plateau (“pagoda-type”, determined by JLCA and MTPD) and advanced K/L grade were the indication criteria recommended by several reports and verified in our study [ 13 , 16 ]. However, to the best of our best knowledge, no study has taken the alignment of lower limb and the accurate value of the certain parameters into consideration.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The shape of tibia plateau (“pagoda-type”, determined by JLCA and MTPD) and advanced K/L grade were the indication criteria recommended by several reports and verified in our study [ 13 , 16 ]. However, to the best of our best knowledge, no study has taken the alignment of lower limb and the accurate value of the certain parameters into consideration.…”
Section: Discussionsupporting
confidence: 80%
“…During TCVO, we discovered that elevation of the medial tibia plateau could help recover the tension of MCL and subsequently loosen the LCL as the lower limb alignment was restored. Furthermore, a previous study also reported increased tension in the cruciate ligaments which contributed to increased joint stability [ 13 ]. Thus, TCVO does not require additional ligament reconstruction to improve joint stability and congruency.…”
Section: Discussionmentioning
confidence: 99%
“…In normal knees, the JLCA ranges from 0° to 2°. 13 However, the parallel JLCA differs in patients with medial osteoarthritis because of varus alignment, with pseudolaxity of the lateral side resulting from substantial amounts of intra-articular cartilage loss in the medial compartment. 27 , 36 In medial laxity knees with varus alignment, the difference in values between JLCA while standing and on application of valgus force could be significantly large.…”
Section: Discussionmentioning
confidence: 99%
“…The image of the right knee joint revealed grade 4 OA on the Kellgren-Lawrence scoring system, with a bone defect in the medial tibia. The shape of the tibial plateau was a pagoda-type, and the medial tibial plateau depression (MTPD) [3] was −40 °(Figure 2). Full-length radiography of the lower limbs showed pelvic tilt and genu varum, with a femorotibial angle of 182 °(Figure 3).…”
Section: Report Of the Casementioning
confidence: 99%